Egisto pastor: un epiteto ‘polisemico’? - Paola Tempone (Exemplaria Classica, 2017)
In Dracontius’ Orestis tragoedia, Egistus is often called pastor. This may be related to his rural origins, as, even if noble, he was abandoned as a child and brought up by some shepherds. Further more there may be other interpretations. Starting from the analysis of the polysemic value of the word pastor, particularly in its meaning of dux (served in the homeric tag ?????? ????) here are proposed more lectures of this title, considering Dracontius’ rethoric and scholastical education, and the attention to poetic lusus in late ancient poetry.